Risk causation model to capture and transfer knowledge in international construction projects - Zhu, Fengfeng; Hu, Hao; Xu, Feng (Journal of Civil Engineering and Management, 2022)
International construction projects are facing various severe risks from country, partner, company, and project. Global contractors have suffered heavy losses. Previous researches have proved that an available organizational risk repository is a reliable knowledge source that can be used to introduce experience-based solutions of how specific risks can be managed in international construction projects. The construction of the organizational risk repository calls for an effective feedback mechanism that dispels the organizational culture of unwillingness to disclose management failure and encourages proactive creation and retention of data and information on historical projects and risk-related knowledge. Hence, this paper proposes a risk causation model for international construction projects (RCM_ICP) to support such a mechanism. RCM_ICP links response measures to the chain of risks to identify management failures and conduct modifications, thereby promoting thinking on the part of the management and capturing key risk management experiences. It includes a category component for the efficient retrieval of relevant knowledge based on country-related factors. Besides, this paper proposes the risk review procedures as the instruction of RCM_ICP. Hence, this research breaks the barriers of sharing information between project and organization levels in a project-based industry.